Transient prenatal ruxolitinib treatment suppresses astrogenesis during development and improves learning and memory in adult mice - Han-Chung Lee (Nature Portfolio, 2021)
Abstract Ruxolitinib is the first janus kinase 1 (JAK1) and JAK2 inhibitor that was approved by the United States Food and Drug Administration (FDA) agency for the treatment of myeloproliferative neoplasms. The drug targets the JAK/STAT signalling pathway, which is critical in regulating the gliogenesis process during nervous system development. In the study, we assessed the effect of non-maternal toxic dosages of ruxolitinib (0–30 mg/kg/day between E7.5-E20.5) on the brain of the developing mouse embryos. While the pregnant mice did not show any apparent adverse effects, the Gfap protein marker for glial cells and S100β mRNA marker for astrocytes were reduced in the postnatal day (P) 1.5 pups' brains. Gfap expression and Gfap+ cells were also suppressed in the differentiating neurospheres culture treated with ruxolitinib. Compared to the control group, adult mice treated with ruxolitinib prenatally showed no changes in motor coordination, locomotor function, and recognition memory. However, increased explorative behaviour within an open field and improved spatial learning and long-term memory retention were observed in the treated group. We demonstrated transplacental effects of ruxolitinib on astrogenesis, suggesting the potential use of ruxolitinib to revert pathological conditions caused by gliogenic-shift in early brain development such as Down and Noonan syndromes.